Case Study of Modular Pre-cast Concrete On-Site Stormwater Detention Susyem during Monsoon Season in Southeast Asia - Mah, D.Y.S.; Ngu, J.O.K.; Bustami, R.A.; Putuhena, F.J. (Environmental Research Institute, Chulalongkorn University, 2021)
On-site stormwater detention system within a residential property is meant for an environmental protection device that temporarily stores stormwater within the property lot to mitigate flash flood, particularly during rainy seasons brought by the Northeast Monsoon. A field test was constructed in a house’s car porch with a 4.40 m x 4.70 m x 0.45 m tank filled with precast-concrete modular units with an effective storage volume of 3.97 m3. The system received water from a 95 m2 house roof via 0.1 m diameter pipe, discharged water via 0.05 m diameter pipe. It had recorded six observed storm events coincided with the 2019/2020 monsoon season that consisted 20-50 mm peak hourly rainfall, 0.0007-0.0018 m3s-1 inflow, 0.0005-0.0012 m3s-1 outflow and 0.21-0.47 m water level. Another four historical storm events coincided with the monsoon from 2015-2017 were sourced to augment the analysis. A computer model developed using the Storm Water Management Model was calibrated and verified using the six observed events. The Kolmogorov-Smirnov goodness of fit tests between the observed and modelled cumulative distributions had produced 0.01-0.14 maximum vertical distances that were lower than the 0.41-0.68 critical values indicating close matches. As such, the calibrated and verified model was used to simulate the historical storm events with 40-50 mm peak hourly rainfall and produced 0.0010-0.0013 m3s-1 inflow, 0.00072-0.00076 m3s-1 outflow and 0.41-0.45 m water level. By combining the field test and computer simulation model, it was found the system was able to contain all stormwaters from Northeast Monsoon. However, it had a weakness which the system was approaching its maximum capacity once the peak hourly rainfall exceeded 45 mm. With such a procedure in place, improvement could be carried out.